Additions of new taxa and record of Dasyhelea Kieffer (Diptera: Ceratopogonidae) from West Bengal, India - Brahma, Shubhranil; Chatterjee, Somnath; Pal, Gouri Sankar; Díaz, Florentina; Hazra, Niladri (Zootaxa, 2025)
Three new species, Dasyhelea (Dicryptoscena) becca, D. (Pseudoculicoides) fusiformis, and D. (Ps.) projectura are described from the Ganges deltaic region of West Bengal, India. Additionally, the species Dasyhelea (Dasyhelea) bambusaoris Yu is reported for the first time from India, which was collected from the Eastern Himalaya Biodiversity Hotspot. With the discovery of these three new species and one new record, the total number of Dasyhelea species in India rises to 33. We provide a brief account of the bionomics and study areas.